Influence of Parents’ English Mastery on Children’s Screen Time for English Learning - Putri, Happy Andita; Kalisa, Pasca (Journal of English Language and Education, 2025)
This study investigates the influence of parents' English mastery on children's screen time for learning English, considering the mediating role of parental involvement. A quantitative correlational design was used in this study with 38 participants consisting of parents of students at Al Madina Islamic Kindergarten in Semarang. Data were collected through a questionnaire via Google form and analyzed using Spearman's correlation. The results showed a significance value of p = 0.059 for the correlation between parents' English proficiency and screen time frequency, and a significance value of p = 0.009 for the correlation between parents' English proficiency and parental involvement. This indicates that parents' English proficiency is not significantly related to children's screen time frequency but is significantly correlated with parental involvement. This study emphasizes the importance of empowering parents not only with language skills but also with active involvement strategies.